A Statistical Analysis of the Hallucination Hypothesis Used to Explain the Resurrection of Christ - Gerald Fudge (Religions)
Given the centrality of the resurrection to the Christian faith, the post-crucifixion appearances of Jesus to his disciples continue to be a central topic in historical inquiry regarding the origins of the Christian faith. While a number of hypotheses have been proposed for these post-crucifixion appearances, a leading naturalistic explanation suggests that these appearances are best explained by grief-induced bereavement hallucinations. Although scholars acknowledge that such hallucinations are somewhat unlikely, prior works have not provided a quantitative analysis of the hallucination hypothesis, so the question remains: Just how improbable is the hallucination hypothesis? This paper presents a statistical analysis to address this question for some of the hallucination scenarios proposed by scholars to show that the probabilities are extremely low, even given mitigating circumstances.